Backpacker Tourist Behavior towards Sustainable Tourism in Yogyakarta - Pitaya Pitaya (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: This research aims to see the relationship between backpacker tourist behavior and the development of sustainable tourism in Yogyakarta. Method: Incorporating the role of backpackers in the context of sustainable tourism is the aim of this study which took a sample of 272 backpackers in a questionnaire regarding attitudes towards sustainable tourism. The data obtained was processed using Ms. Excel and then described narratively. Result: The results show that the majority of backpacker tourists have behavior that strongly supports the concept of sustainable tourism in Yogyakarta. Contribution: This study provides empirical evidence that backpacker tourists positively support sustainable tourism in Yogyakarta, offering valuable insights for policymakers and stakeholders in promoting sustainable tourism development.